Sustained antiviral insulin signaling during West Nile virus infection results in viral mutations - Char, Aditya B.; Trammell, Chasity E.; Fawcett, Stephen; Chauhan, Manish; Debebe, Yared; Céspedes, Nora; Paslay, Ryder A.; Ahlers, Laura R. H.; Patel, Dharmeshkumar; Luckhart, Shirley; Goodman, Alan G. (Frontiers in Cellular and Infection Microbiology, 2024)
Arthropod-borne viruses or arboviruses, including West Nile virus (WNV), dengue virus (DENV), and Zika virus (ZIKV) pose significant threats to public health. It is imperative to develop novel methods to control these mosquito-borne viral infections. We previously showed that insulin/insulin-like growth factor-1 signaling (IIS)-dependent activation of ERK and JAK-STAT signaling has significant antiviral activity in insects and human cells. Continuous immune pressure can lead to adaptive mutations of viruses during infection. We aim to elucidate how IIS-signaling in mosquitoes selects for West Nile virus escape variants, to help formulate future transmission blocking strategies. We hypothesize that passage of WNV under activation of IIS will induce adaptive mutations or escape variants in the infecting virus. To test our hypothesis, WNV was serially passaged through Culex quinquefasciatus Hsu cells in the presence or absence of bovine insulin to activate IIS antiviral pressure. We sequenced WNV genes encoding for E, NS2B, NS3, and NS5 and identified variants in E and NS5 arising from IIS antiviral pressure. In parallel to the genetic analyses, we also report differences in the levels of virus replication and Akt activation in human cells and mosquitoes using virus passaged in the presence or absence of insulin. Finally, using adult Culex quinquefasciatus, we demonstrated the enhancement of immune response gene expression in virus-infected mosquitoes fed on insulin, compared to control. Notably, virus collected from insulin-fed mosquitoes contained a non-synonymous mutation in NS3. These results contribute towards achieving our long-term goal of manipulating mosquito IIS-dependent antiviral immunity to reduce WNV or other flavivirus transmission to mammalian hosts.